(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The present study aims to investigate has been implemented of advertising on the buying behavior consumers for date seed oil using theory planned behavior (TPB). The present study is descriptive of the type of correlation. The study population consisted of all consumers in Kerman. The total samples were 384 people in this research that have participate 82 person in the male group c and 302 person in the female group .A multistage cluster sampling method was used to implement the questionnaire. In this research, descriptive statistical methods such as tables, frequency percentages, mean and standard deviations, and normality and hypothesis testing were confirmed. As a result, all hypotheses were confirmed and indicate the positive and significant hypotheses of the advertising on the variables others that advertising is having significantly and positive effect on the attitude, perceived behavioral control and Subjective norm toward consumer buying behavior and at the end of, advertising have the role of a mediator test toward consumer buying behavior.